Neurotensin agonist alleviates metabolic disturbance, neuropathology, and cognitive decline in high‐fat diet–induced obese rats: Molecular and cell biology: Neurodegeneration versus neuroprotection. (7th December 2020) - Saiyasit, Napatsorn; Chunchai, Titikorn; Apaijai, Nattayaporn; Pratchayasakul, Wasana; Sripetchwandee, Jirapas; Chattipakorn, Nipon; Chattipakorn, Siriporn C.
Abstract: Background: Previous studies demonstrated that chronic high‐fat diet (HFD) consumption caused the development of obesity with metabolic disturbance, systemic inflammation, neuropathologies, including cognitive impairment and the disruption of brain neurotensin (NT) signaling. Moreover, exogenous NT treatment showed the neuroprotective effects and improved cognitive function in genetic‐induced obese models. However, the effect of NT agnoist on peripheral/brain pathologies following long‐term HFD consumption has not been investigated. The present study hypothesizes that NT agonist alleviates the aforementioned adverse effects in both periphery and brain in HFD‐fed rats. Method: Male Wistar rats were received either a normal diet (ND) or HFD for 16 weeks. At week 13, ND‐fed rats were received the saline solution as a vehicle group (n=4‐6). HFD‐fed rats were randomly divided into 2 subgroups to receive either a vehicle or 1 mg/kg of PD149163 (NT agonist) via subcutaneous injection consecutively for 2 weeks (n=4‐6/group). At week 15, Morris water maze (MWM) test, and blood collection were performed, then animals were sacrificed. The metabolic parameters and peripheral inflammation were examined. Reactive oxygen species (ROS) production, dendritic spine density, number of microglia, and Alzheimer's‐related protein expression in hippocampus were also determined. Result: 16‐week HFD‐fed rats developed obesity with peripheral insulin insensitivity, and increased level of serum lipopolysaccharide (LPS). Furthermore, a cognitive decline as demonstrated by the increased time to reach the platform and decreased time spent in the target quadrant from the MWM test (Figure 1A), increased number of Iba1 + cells (Figure 1B), elevated the levels of hippocampal ROS (Figure 1C), and increased the expression of p‐Tau Thr181 protein (Figure 1D), as well as reduced dendritic spine density were observed when compared to ND‐fed rats. Interestingly, the administration of NT agonist restores the aforementioned negative parameters in both periphery and brain in HFD‐fed rats (Figure 1A‐D). Conclusion: These findings suggest that the administration of NT agonist alleviates peripheral pathologies and exerts neuroprotective effects by decreasing the expression of Alzheimer's‐related protein, reducing brain inflammation/oxidative stress, and restoring cognitive function in obese insulin‐resistant rats. Therefore, NT should be a therapeutic target to prevent cognitive impairment in obese people.